The Effectiveness of Ebselen in Facial Nerve Crush Injury: An Experimental Study - Lütfü Şeneldir; Veysel Alparslan Gölcük; Gökçe Tanyeri Toker; Ayşegül Verim; Pembegül Güneş (Journal of International Advanced Otology)
Background: Ebselen is a neuroprotective drug that protects cellular components from oxidative damage by modulating enzymatic cofactors, metalloproteins, gene expression, antioxidant-anti-inflammatory effects, and immunological systems. Our goal was to compare the efficacy of Ebselen and methylprednisolone on rat facial nerve crush injury.